Raman, FTIR, UV-Visible and FESEM Studies on Calix[8]arene Embedded Multi-walled Carbon Nanotubes Nanocomposites using Spin Coating Technique - Razali, Amira Shakila; Supian, Faridah Lisa; Al Naim, Abdullah F.; Ayop, Shahrul Kadri; Azahari, Noor Azyyati (Journal of Science and Mathematics Letters, 2021)
In this research, the preparation and characterization of the organic compound calix[8]arene (TBC8) are embedded with multi-walled carbon nanotubes (MWCNTs) using spin coating technique. The nanocomposites were prepared layer by layer, where TBC8 was dissolved in chloroform solution (0.2 mg/mL), followed by the additional layer of MWCNTs in the upper nanocomposites. We have explored the effects of TBC8 being modified with MWCNTs by Raman, where the crystallinities of the nanocomposites were observed. By Fourier Transform Infrared (FTIR) analysis, the nanocomposites' characteristic patterns have been detected. Ultraviolet-visible spectroscopy defines the fingerprints and the shifting of the nanocomposites while Field Emission Scanning Electron Microscope (FESEM) determines the structural morphology. The TBC8 attached to the MWCNTs has a future potential application for the development of the sensor in pollutant monitoring nano-electronics devices.